Abrasion resistance of thermally and chemically modified timber : Otpornost toplinski i kemijski modificiranog drva na habanje - Brischke, Christian (Array, 2019)
Wood modification is an appropriate way of improving the natural durability and dimensional stability of wood without the use of biocides. Different thermal and chemical wood modification processes are available for this purpose, very differently affecting the structural integrity of wood. In this study, thermally modified, melamine resin treated, acetylated, furfurylated, and mDMDHEU treated wood underwent abrasion tests according to two different methods representing different loads in practice. The Taber Abraser method caused crosswise cutting into the wood surface, while the Shaker method challenged mainly the specimen edges with dynamic loads. Abrasion resistance of wood was affected by all types of cell wall modification, but the effects were strongly dependent on the type of modification and the applied load type. For characterising the suitability of wooden materials with respect to wear resistance under outdoor conditions, it is recommended to apply a set of methods rather than a single test procedure to fully reflect the loads occurring in practice.